Pedagogical Exemplars for Mathematics Across Learning Styles - Ocampo, Evelina N.; Siahaan, Kevin William Andri; Sinaga, Samuel Juliardi; Cutillas, Anesito L. (research, training and philanthropy institution Natural Aceh, 2023)
This study investigated the effectiveness of different pedagogical exemplars for teaching mathematics across various learning styles using multimedia technology. The study utilized a quasi-experimental design. The experimental group received the intervention through an interactive computer presentation program, while the control group used the standard dialogue and discussion techniques. The study used survey questionnaires adapted from BARSCH's Learning Style Inventory and self-made pre-and post-tests to measure students' learning and engagement. The research findings revealed that students with different learning styles benefited differently from multimedia-assisted instruction, suggesting the importance of considering individual differences in instructional design. The use of multimedia technology in teaching mathematics facilitates the learning process of students with different learning styles. The results of this study also support the importance of using statistical analysis to evaluate the effectiveness of educational interventions and to inform evidence-based decision-making in education. This study identified the most effective pedagogical exemplars for each learning style and highlighted the benefits of interactive media teaching mathematics. These findings suggest that teaching methods that align with students' learning styles can improve academic performance